The labor market in Ireland, 2000-2018 - Adele Bergin; Elish Kelly; Paul Redmond (IZA World of Labor, 2020)
Ireland was hit particularly hard by the global financial crisis, with severe impacts on the labor market. Between 2007 and 2013, the unemployment rate increased dramatically, from 5% to 15.5%, and the labor force participation rate declined by almost five percentage points between 2007 and 2012. Outward migration re-emerged as a safety valve for the Irish economy, helping to moderate impacts on unemployment via a reduction in overall labor supply. As the crisis deepened, long-term unemployment escalated. However, since 2013, there is clear evidence of a recovery in the labor market with unemployment, both overall and long-term, dropping rapidly.
Keywords: J1; J8; J21; J60; J64; J68; 330; unemployment; migration; Brexit; Ireland